Associations between dietary patterns and metabolic syndrome in adolescents - Guadalupe Ramírez-López; Mario Flores-Aldana; Jorge Salmerón (Instituto Nacional de Salud Pública, 2019)
Objective. Evaluate association of dietary patterns with metabolic syndrome (MetS) and metabolic markers. Materials and methods. 654 adolescents from Guadalajara, Jalisco, participated in a cross-sectional study. Diet was evaluated using a food frequency questionnaire; 24 food groups were integrated, and dietary patterns were derived using cluster analysis. MetS was defined according to International Diabetes Federation (IDF), Cook and colleagues, Ford and colleagues, and de Ferranti and colleagues criteria. Results. Dietary patterns identified were: "DP1", "DP2", and "DP3". Among males, "DP3" was associated with MetS (Cook and collaborators) (OR, 12.14; 95%CI, 1.66-89.05), hypertriglyceridemia (OR, 3.89; 95%CI, 1.01-15.07), and insulin resistance (OR, 6.66; 95%CI, 1.12-39.70). "DP2" was associated with abdominal obesity (OR, 5.11; 95%CI, 1.57-16.66). Conclusions. "DP3" entertained a greater risk of MetS, hypertriglyceridemia, and insulin resistance, while "DP2" possessed a greater risk of abdominal obesity among adolescent males.